Purchase Intention of Electric Vehicles: A Systematic Literature Review - Junaedi, Didi; Pujiyanto, Eko; Hisjam, Muhammad; Damayanti, Retno Wulan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This research aims to a systematic review and bibliometric analysis in electric vehicles topic. The analysis involved 325 articles published in the Scopus database from 1994 to 2023. The analysis examines the results of the study by observing trends in journals, authorship, and keywords. The results were visualized using VOSviewer to show graphical network keywords and using a spreadsheet application. The results show that this research area has expanded over a period of five years, namely 2019-2023. The leading journal in this field between 2019 and 2023, is Sustainability (Switzerland) followed by Energy Policy and Journal Research in Transportation Business and Management. Content analysis consists of the country where the research is conducted, the research subjects, the theoretical approach used, and the method. Based on the country where the study is China, followed by India, Malaysia, Thailand, and Indonesia. The subject of research on electric cars dominates when compared to other electric vehicles. The methods used are quite diverse in developing the model, so that studies on electric vehicles can still be developed in the future.